A phase I study comparing the pharmacokinetics and safety of HS628 (tocilizumab biosimilar) and reference tocilizumab in healthy male subjects - Hongjie Qian; Jie Cheng; Yuzhou Gui; Wei Wang; Liyu Liang; Huijuan Zhu; Qingqing Wu; Meixian Ou; Qian Chen; Chen Yu; Jingying Jia (Wiley, 2023)
Abstract This study aimed to evaluate the pharmacokinetic (PK) similarity of the proposed biosimilar HS628 compared with the reference tocilizumab (Actemra®) and also to demonstrate similar safety and immunogenicity profiles in healthy Chinese male subjects. Eighty eligible subjects were randomized into two treatment groups in a 1:1 ratio to receive a single intravenous infusion of HS628 or tocilizumab at 4 mg/kg over 60 min. Blood samples were collected at the scheduled time points for PK and immunogenicity analysis. PK biosimilarity was determined using the standard bioequivalence criteria 80%-125%. A total of 77 subjects received the study drug and completed the study. The main PK parameters were similar for the test and reference groups. The ratio of geometric least‐squares means (GMR) and its 90% CIs for AUC0-t, AUC0-∞, and Cmax between the test group and reference group were 1.06 (1.00-1.12), 1.07 (1.00-1.14), and 1.04 (0.99-1.10), respectively, which were fully within the predefined bioequivalent range of 80%-125%. The incidence of treatment‐emergent adverse events (TEAEs) was similar for HS628 and tocilizumab (p > 0.05). The most common TEAEs were decreased fibrinogen, decreased neutrophils, pharyngalgia, oral ulcer, decreased leukocytes, and increased erythrocyte sedimentation rate. The results of the present study provide strong evidence to support the PK similarity and bioequivalence of HS628 and tocilizumab. The safety and immunogenicity profiles of HS628 were also shown to be similar to those of the reference tocilizumab.